Downregulation of dual‐specificity tyrosine‐regulated kinase 2 promotes tumor cell proliferation and invasion by enhancing cyclin‐dependent kinase 14 expression in breast cancer. Issue 2 (13th January 2018) - Imawari, Yoshimi; Mimoto, Rei; Hirooka, Shinichi; Morikawa, Toshiaki; Takeyama, Hiroshi; Yoshida, Kiyotsugu
Abstract : Tumor progression is the main cause of death in patients with breast cancer. Accumulating evidence suggests that dual‐specificity tyrosine‐regulated kinase 2 (DYRK2) functions as a tumor suppressor by regulating cell survival, differentiation, proliferation and apoptosis. However, little is known about the mechanisms of transcriptional regulation by DYRK2 in cancer progression, particularly with respect to cancer proliferation and invasion. Here, using a comprehensive expression profiling approach, we show that cyclin‐dependent kinase 14 (CDK14) is a target of DYRK2. We found that reduced DYRK2 expression increases CDK14 expression, which promotes cancer cell proliferation and invasion in vitro, in addition to tumorigenicity in vivo. CDK14 and DYRK2 expression inversely correlated in human breast cancer tissues. We further identified androgen receptor (AR) as a candidate of DYRK2‐dependent transcription factors regulating CDK14. Taken together, our findings suggest a mechanism by which DYRK2 controls CDK14 expression to regulate tumor cell proliferation and invasion in breast cancer. Targeting of this pathway may be a promising therapeutic strategy for treating breast cancer. Abstract : DYRK2 suppresses tumor cell proliferation and invasion by inhibiting CDK14 transcription, and reduced DYRK2 expression in invasive ductal carcinoma promotes tumor cell proliferation and invasion through CDK14 expression via transcriptional regulation by AR.